Metal–Organic Frameworks Based on Group 3 and 4 Metals. Issue 44 (9th September 2020) - Feng, Liang; Pang, Jiandong; She, Ping; Li, Jia‐Luo; Qin, Jun‐Sheng; Du, Dong‐Ying; Zhou, Hong‐Cai
Abstract: Metal–organic frameworks (MOFs) based on group 3 and 4 metals are considered as the most promising MOFs for varying practical applications including water adsorption, carbon conversion, and biomedical applications. The relatively strong coordination bonds and versatile coordination modes within these MOFs endow the framework with high chemical stability, diverse structures and topologies, and interesting properties and functions. Herein, the significant progress made on this series of MOFs since 2018 is summarized and an update on the current status and future trends on the structural design of robust MOFs with high connectivity is provided. Cluster chemistry involving Y, lanthanides (Ln, from La to Lu), actinides (An, from Ac to Lr), Ti, and Zr is initially introduced. This is followed by a review of recently developed MOFs based on group 3 and 4 metals with their structures discussed based on the types of inorganic or organic building blocks. The novel properties and arising applications of these MOFs in catalysis, adsorption and separation, delivery, and sensing are highlighted. Overall, this review is expected to provide a timely summary on MOFs based on group 3 and 4 metals, which shall guide the future discovery and development of stable and functional MOFs for practical applications. Abstract : Metal–organic frameworks (MOFs) based on group 3 and 4 metals with high chemical stability, structural diversity, and various interesting properties are reviewed. Cluster and framework chemistry of group 3 and 4 metals are expected to provide a timely summary on MOF development, which shall guide the discovery and development of stable and functional MOFs for practical applications.